Identification of key genes and pathways in schizophrenia: a bioinformatics analysis based on GWAS and GEO - Shokrgozar, Alireza; Rahimi, Maryam; Shoraka, Shahrzad (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia is a mental illness that is associated with many disorders, such as incoherence of mental activities, and impairment of perception, thinking, emotions, and behavior. Although the exact cause of schizophrenia is unknown, many studies have highlighted the role of genetic background and environmental factors in this disease. Therefore, the identification of key genes involved in schizophrenia provides a promising opportunity to develop novel diagnosis and/or treatment methods. This study aims to investigate schizophrenia-related hub genes by bioinformatics analysis based on genome-wide association (GWAS) and gene expression omnibus (GEO) datasets.Material and methodsIn this study, the GWAS catalog and GEO dataset were used to identify key candidate genes and pathways that are important in the diagnosis and treatment of schizophrenia, and then the results were analyzed using Enrichr and Cytoscape tools.ResultAccording to our result NRXN, CACNA1C, and GRIN2A genes had the highest scores in the GWAS analyses and BRCA1, ATM, and STAT1 genes had the highest scores in the GEO dataset. Also, glucuronidation, ascorbate, and aldarate metabolism pathways in the GWAS, PI3K/AKT and Rap1 signaling in the GEO had the highest associations with schizophrenia.ConclusionThis study highlights the need for further validation of the genes and molecular pathways in schizophrenia. Also, the identified genes could be promising candidates for future diagnostic and/or treatment strategies for schizophrenia.